Nurse job satisfaction at a surgical ward - a comparative study between Sweden and Poland - Lena Serafin; Kristofer Bjerså; Anna Doboszyńska (Nofer Institute of Occupational Medicine, 2019)
Background Job satisfaction is a major issue in work psychology among nurses, and in the surgical nursing context, important factors leading to the perception of job satisfaction have been suggested. Two European Union neighboring countries (Sweden and Poland) were chosen for the purpose of this study due to similar nursing education but different health care systems, employment regulations and salaries. Recognition of the factors which are related to nurse job satisfaction may lead to improvements in the nurses' working conditions. The aim of this study was to explore and compare job satisfaction and various factors among Polish and Swedish nurses in a surgical ward context. Material and Methods The study had a cross-sectional survey design, with questionnaires among Polish and Swedish nurses in surgical care, and was conducted between April and December 2014. The main assessment tool was a Job Satisfaction Survey questionnaire. In total, 408 nurses returned the questionnaire (response rate - 59%). Results Swedish nurses rated job satisfaction significantly higher than Polish nurses. The possibilities for professional development at the current workplace correlated with job satisfaction in both groups. Higher values of exhaustion due to nurses' working duties were correlated with general job satisfaction. Conclusions Swedish and Polish nurses showed ambivalence towards job satisfaction. Their job satisfaction increased when their exhaustion level was higher. The possibilities for achievements, developing professional skills, and promotion may be important factors affecting job satisfaction. Med Pr. 2019;70(2):155-67